A new type of high wear-resistant and high-strength cemented carbide formula and production process
By adopting new cemented carbide formulas and fine grinding technology with diverse components, the problem of the microstructure of traditional cemented carbide is solved, and the strength and wear resistance of cemented carbide is significantly improved. It is suitable for high-speed cutting and high-strength grinding and other scenarios.
Patent Information
- Application Number
- CN202411930184.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
During the preparation process, traditional cemented carbides have a coarse particle size of the raw material powder, which leads to the microstructure formed after sintering, with high porosity, making it difficult to achieve high strength and wear resistance, and cannot adapt to precision and efficient processing scenarios such as high-speed cutting and high-strength grinding.
The new high-wear-resistant and high-strength cemented carbide formula is adopted, including nano-titanium carbide, nano-titanium nitride, tungsten carbide, niobium carbide, silicon carbide, cobalt powder, yttrium oxide, boron carbide and copper powder, and a denser and uniform microstructure is formed through fine grinding technology and multi-step sintering process.
It significantly improves the strength and wear resistance of cemented carbide, can more effectively resist external friction and cutting forces, extend service life, and show excellent mechanical properties under high load working conditions.
Smart Images

Figure CN119736535A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cemented carbide production, in particular to a novel high-wear-resistant and high-strength cemented carbide formula and production process. Background Art
[0002] In many fields of modern industry, such as mechanical processing, mining, aerospace, etc., the performance requirements for cemented carbide are becoming increasingly stringent. Although traditional cemented carbide has met the basic wear resistance and strength requirements to a certain extent, its limitations have become increasingly prominent with the rapid development of technology. On the one hand, during the preparation process of conventional cemented carbide, due to the coarse particle size of the raw material powder, the general tungsten carbide particle size is 1-5μm, resulting in the microstructure formed after sintering is not dense enough and the porosity is relatively high, which makes it difficult for the strength and wear resistance of cemented carbide to reach higher standards and cannot adapt to precision and efficient processing scenarios such as high-speed cutting and high-intensity grinding. On the other hand, the traditional formula ingredients are relatively single, mostly based on common tungsten carbide and cobalt powder, lacking a diverse and synergistically optimized combination of ingredients, and it is difficult to comprehensively improve the key properties of the alloy. When dealing with complex working conditions, such as long-term use in high temperature and highly corrosive environments, it is easy to have problems such as premature wear and strength reduction. For this reason, we propose a new high-wear-resistant and high-strength cemented carbide formula and production process. Summary of the invention
[0003] The purpose of the present invention is to provide a novel high wear-resistant and high strength cemented carbide formula and production process to solve the problems raised in the above background technology.
[0004] To achieve the above object, the present invention provides the following technical solution: a new high wear-resistant and high strength cemented carbide formula, comprising:
[0005] 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride, 7-9 parts of tungsten carbide, 5-8 parts of niobium carbide, 3-7 parts of silicon carbide, 3-5 parts of cobalt powder, 1-3 parts of grain growth inhibitor, 1-3 parts of boron carbide, and 1-5 parts of copper powder;
[0006] Among them, yttrium oxide is used as the grain growth inhibitor.
[0007] A novel high-wear-resistant and high-strength cemented carbide production process, the novel high-wear-resistant and high-strength cemented carbide production process comprising the following steps:
[0008] S1. Prepare materials: 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride, 7-9 parts of tungsten carbide, 5-8 parts of niobium carbide, 3-7 parts of silicon carbide, 3-5 parts of cobalt powder, 1-3 parts of yttrium oxide, 1-3 parts of boron carbide, and 1-5 parts of copper powder. The particle size of tungsten carbide is 2.0-5.0 μm, the particle size of cobalt powder is 1.5-3.5 μm, the particle size of copper powder is 1.8-3.5 μm, the particle size of yttrium oxide is 1.0-3.0 μm, and the particle sizes of niobium carbide, silicon carbide, and boron carbide are 1.5-3.5 μm.
[0009] S2. Prepare carbon-poor alloy powder by mixing the weighed raw materials uniformly, and reducing them in a hydrogen atmosphere at 900-1050° C. for 45-75 min to obtain carbon-poor alloy powder;
[0010] S3, preparing a pre-sintered matrix, first wet-milling the carbon-poor cemented carbide powder, the ball milling medium is alcohol, the liquid-solid ratio of alcohol to powder is 400-600mL / kg, the ball-to-material ratio of ball milling is 4-6:1, the ball mill speed is controlled at 50-100 rpm, the ball milling time is controlled at 15-20h, after the wet milling is completed, the slurry is filtered, and a spray dryer is used for atomization drying and granulation, and then the granulated powder is pressed and formed at 150-200MPa, and pressure sintered at 1430-1445°C and a pressure of 8-10 MPa for 50-75 minutes to obtain a carbon-poor pre-sintered matrix;
[0011] S4, carburizing treatment, placing the pre-sintered substrate in a hydrogen atmosphere, using dense crystalline graphite as a carbon source, and performing carburizing treatment at 1420-1450° C. for 60-100 minutes to obtain a carburized cemented carbide;
[0012] S5, firing, ball-milling the carburized cemented carbide into powder of 0.1-5 μm, loading it into a cemented carbide mold, and then placing it into a spark plasma sintering device for low-temperature and high-pressure sintering.
[0013] Preferably, the raw materials prepared in S1 are dried in a vacuum environment to ensure that adsorbed moisture and impurities are removed to prevent defects such as pores from being generated during subsequent processing.
[0014] Preferably, the S2 is used to prepare the carbon-poor alloy powder. During mixing, a dry ball mill is used for mixing. The ball-to-material ratio is controlled at 3:1, the mixing speed is controlled at 50-200 rpm, and the mixing time is controlled at 3-8h to ensure uniform mixing.
[0015] Preferably, the S5 is placed in a spark plasma sintering device for low-temperature and high-pressure sintering, the sintering pressure is controlled at 100-300 MPa, the temperature is increased from room temperature to 100°C, the heating rate is 10-50°C / min, and it is kept at 100°C for 10-30 min. After the insulation is completed, the temperature is increased from 100°C to 300°C, the heating rate is 10-50°C / min, and it is kept at 300°C for 10-30 min. After the insulation is completed, the sintering pressure is increased to 300-500 MPa, and under this pressure, the temperature is increased from 300°C to 500-700°C, the heating rate is 10-100°C / min, and it is kept at 500-700°C for 30-60 min.
[0016] Preferably, the pre-sintered block in the cemented carbide mold obtained in S5 is placed in a high-strength graphite mold, and placed in a spark plasma sintering device for densification sintering, so as to finally obtain a composite cemented carbide for tool material.
[0017] Preferably, the densification sintering is carried out in a spark plasma sintering device, the sintering pressure is controlled to be 70-240MPa, the heating rate is 50-100℃ / min, the sintering temperature is 980-1040℃, and the temperature is kept at 980-1040℃ for 1-3min. After the insulation, the temperature is cooled to 300℃ at a cooling rate of 10-100℃ / min, and then cooled to room temperature with the furnace.
[0018] Preferably, the S2 raw material mixing comprises the following specific steps:
[0019] S2.1. Place the raw materials in a ball mill for dry ball milling to fully mix the raw materials and obtain a mixed powder;
[0020] S2.2. Place the mixed powder into a high temperature resistant reaction vessel, and then place it in a hydrogen reduction furnace, ensuring that the vessel is placed stably and has enough space for hydrogen circulation around it;
[0021] S2.3. Before heating, slowly introduce hydrogen into the reduction furnace to remove the air in the furnace and prevent oxidation reaction between oxygen and raw materials. The speed of introducing hydrogen needs to be controlled to avoid blowing away the powder due to excessive speed. When the air in the furnace is basically exhausted, speed up the hydrogen flow to maintain a stable hydrogen atmosphere in the furnace.
[0022] S2.3, turn on the heating device, raise the temperature in the furnace to 900-1050°C at a certain heating rate, and maintain it within this temperature range for 45-75 minutes, so that the oxides in the raw materials undergo a reduction reaction in the hydrogen atmosphere to generate corresponding metals or alloys, thereby obtaining carbon-poor alloy powder;
[0023] S2.4. After the reduction reaction is completed, stop heating and allow the furnace to cool naturally or cool to room temperature with the furnace under a protective atmosphere. Stop introducing hydrogen only when the temperature in the furnace drops below the safe temperature. Then carefully take out the reaction vessel to obtain the prepared carbon-poor alloy powder.
[0024] Preferably, in the material preparation stage, S1 adopts a vibration ball milling method, through the high-frequency vibration of the ball mill, the grinding balls generate strong vibration impact in the mill, and then the powder is ground and crushed, so as to control the particle size of the raw material. Finer powder can form a denser microstructure after sintering, which helps to improve strength and wear resistance.
[0025] Compared with the prior art, the present invention provides a new high wear-resistant and high-strength cemented carbide formula and production process, which has the following beneficial effects:
[0026] 1. The new high wear-resistant and high-strength cemented carbide formula and production process adopts fine grinding technology, such as vibration ball milling to refine the raw material particle size, especially to reduce the average particle size of tungsten carbide powder to below 0.5μm, and cooperates with a unique formula system, 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride and other multi-components to work synergistically. During the sintering process, these ultra-fine powders can be closely arranged to form a more dense and uniform microstructure, which greatly reduces the generation of micro defects during the wear process, effectively resists external friction and cutting force, and significantly extends the service life of cemented carbide under high-load working conditions.
[0027] 2. This new type of high-wear-resistant and high-strength cemented carbide formula and production process, by adding grain growth inhibitors, accurately controls grain growth during the sintering stage, avoids excessive grain growth, and ensures that the microstructure of the cemented carbide matrix is stable and uniform.
[0028] 3. The formula and production process of this new type of high wear-resistant and high-strength cemented carbide, from raw material processing to multi-step sintering process, such as high-temperature hydrogen reduction and step-by-step pressure sintering when preparing carbon-poor alloy powder, promote the full fusion and densification of various components. Ultimately, the cemented carbide has excellent internal bonding strength, and its compressive strength and bending strength are significantly enhanced compared to traditional products. It can withstand greater mechanical loads and performs well in application scenarios with extremely high strength requirements such as heavy tools and mold inserts, effectively reducing the risk of fracture failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the production process of the present invention;
[0030] Figure 2 This is a schematic diagram of the specific steps of preparing carbon-poor alloy powder according to the present invention;
[0031] Figure 3It is a schematic diagram of the specific firing steps of the present invention. DETAILED DESCRIPTION
[0032] like Figure 1-Figure 3 As shown, the present invention provides a technical solution: a new high wear-resistant and high strength cemented carbide production process, the new high wear-resistant and high strength cemented carbide production process comprises the following steps:
[0033] S1. Prepare materials: 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride, 7-9 parts of tungsten carbide, 5-8 parts of niobium carbide, 3-7 parts of silicon carbide, 3-5 parts of cobalt powder, 1-3 parts of yttrium oxide, 1-3 parts of boron carbide, and 1-5 parts of copper powder. The particle size of tungsten carbide is 2.0-5.0 μm, the particle size of cobalt powder is 1.5-3.5 μm, the particle size of copper powder is 1.8-3.5 μm, the particle size of yttrium oxide is 1.0-3.0 μm, and the particle size of niobium carbide, silicon carbide and boron carbide is 1. The particle size is 1.5-3.5μm. The prepared raw materials are dried in a vacuum environment to ensure the removal of adsorbed moisture and impurities to prevent defects such as pores in the subsequent processing. In the material preparation stage, the vibration ball milling method is adopted. Through the high-frequency vibration of the ball mill, the grinding balls generate strong vibration impact in the mill, and then the powder is ground and crushed, so as to control the particle size of the raw materials. Finer powders can form a denser microstructure after sintering, which helps to improve strength and wear resistance;
[0034] S2. Prepare carbon-poor alloy powder. Mix the weighed raw materials uniformly. Use a dry ball mill to mix. The ball-to-material ratio is controlled at 3:1. The mixing speed is controlled at 50-200 rpm. The mixing time is controlled at 3-8 hours to ensure uniform mixing. Reduce the mixture at 900-1050° C. for 45-75 minutes in a hydrogen atmosphere to obtain carbon-poor alloy powder. The raw material mixing includes:
[0035] S2.1. Place the raw materials in a ball mill for dry ball milling to fully mix the raw materials and obtain a mixed powder;
[0036] S2.2. Place the mixed powder into a high temperature resistant reaction vessel, and then place it in a hydrogen reduction furnace, ensuring that the vessel is placed stably and has enough space for hydrogen circulation around it;
[0037] S2.3. Before heating, slowly introduce hydrogen into the reduction furnace to remove the air in the furnace and prevent oxidation reaction between oxygen and raw materials. The speed of introducing hydrogen needs to be controlled to avoid blowing away the powder due to excessive speed. When the air in the furnace is basically exhausted, speed up the hydrogen flow to maintain a stable hydrogen atmosphere in the furnace.
[0038] S2.3, turn on the heating device, raise the temperature in the furnace to 900-1050°C at a certain heating rate, and maintain it within this temperature range for 45-75 minutes, so that the oxides in the raw materials undergo a reduction reaction in the hydrogen atmosphere to generate corresponding metals or alloys, thereby obtaining carbon-poor alloy powder;
[0039] S2.4. After the reduction reaction is completed, stop heating and allow the furnace to cool naturally or cool to room temperature with the furnace under a protective atmosphere. When the temperature in the furnace drops below the safe temperature, stop introducing hydrogen, then carefully remove the reaction vessel to obtain the prepared carbon-poor alloy powder;
[0040] S3, preparing a pre-sintered matrix, first wet-milling the carbon-poor cemented carbide powder, the ball milling medium is alcohol, the liquid-solid ratio of alcohol to powder is 400-600mL / kg, the ball-to-material ratio of ball milling is 4-6:1, the ball mill speed is controlled at 50-100 rpm, the ball milling time is controlled at 15-20h, after the wet milling is completed, the slurry is filtered, and a spray dryer is used for atomization drying and granulation, and then the granulated powder is pressed and formed at 150-200MPa, and pressure sintered at 1430-1445°C and a pressure of 8-10 MPa for 50-75 minutes to obtain a carbon-poor pre-sintered matrix;
[0041] S4, carburizing treatment, placing the pre-sintered substrate in a hydrogen atmosphere, using dense crystalline graphite as a carbon source, and performing carburizing treatment at 1420-1450° C. for 60-100 minutes to obtain a carburized cemented carbide;
[0042] S5, firing, ball-milling the carburized cemented carbide into powder of 0.1-5 μm, loading it into a cemented carbide mold, and then placing it into a spark plasma sintering device for low-temperature and high-pressure sintering.
[0043] S5 is placed in a spark plasma sintering equipment for low-temperature and high-pressure sintering. The sintering pressure is controlled at 100-300MPa, the temperature is increased from room temperature to 100°C, the heating rate is 10-50°C / min, and it is kept at 100°C for 10-30min. After the insulation is completed, the temperature is increased from 100°C to 300°C, the heating rate is 10-50°C / min, and it is kept at 300°C for 10-30min. After the insulation is completed, the sintering pressure is increased to 300-500MPa. Under this pressure, the temperature is increased from 300°C to 500-700°C, the heating rate is 10-100°C / min, and it is kept at 500-7 The pre-sintered block in the cemented carbide mold is placed in a high-strength graphite mold and placed in a spark plasma sintering device for densification sintering to finally obtain a composite cemented carbide tool material. The composite carbide is placed in a spark plasma sintering device for densification sintering. The sintering pressure is controlled to be 70-240MPa, the heating rate is 50-100℃ / min, the sintering temperature is 980-1040℃, and the mixture is kept at 980-1040℃ for 1-3min. After the insulation is completed, the mixture is cooled to 300℃ at a cooling rate of 10-100℃ / min, and then cooled to room temperature with the furnace.
[0044] A new high wear-resistant and high-strength cemented carbide formula, including:
[0045] 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride, 7-9 parts of tungsten carbide, 5-8 parts of niobium carbide, 3-7 parts of silicon carbide, 3-5 parts of cobalt powder, 1-3 parts of grain growth inhibitor, 1-3 parts of boron carbide, and 1-5 parts of copper powder;
[0046] Among them, yttrium oxide is used as the grain growth inhibitor.
[0047] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.
Claims
1. A new type of high wear-resistant and high-strength cemented carbide formula, characterized by: include: 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride, 7-9 parts of tungsten carbide, 5-8 parts of niobium carbide, 3-7 parts of silicon carbide, 3-5 parts of cobalt powder, 1-3 parts of grain growth inhibitor, 1-3 parts of boron carbide, and 1-5 parts of copper powder; Among them, yttrium oxide is used as the grain growth inhibitor.
2. A new type of high wear-resistant and high-strength cemented carbide production process, characterized by: The novel high wear-resistant and high strength cemented carbide production process comprises the following steps: S1. Prepare materials: 35-40 parts of nano titanium carbide, 5-15 parts of nano titanium nitride, 7-9 parts of tungsten carbide, 5-8 parts of niobium carbide, 3-7 parts of silicon carbide, 3-5 parts of cobalt powder, 1-3 parts of yttrium oxide, 1-3 parts of boron carbide, and 1-5 parts of copper powder. The particle size of tungsten carbide is 2.0-5.0 μm, the particle size of cobalt powder is 1.5-3.5 μm, the particle size of copper powder is 1.8-3.5 μm, the particle size of yttrium oxide is 1.0-3.0 μm, and the particle sizes of niobium carbide, silicon carbide, and boron carbide are 1.5-3.5 μm. S2. Prepare carbon-poor alloy powder by mixing the weighed raw materials uniformly, and reducing them in a hydrogen atmosphere at 900-1050° C. for 45-75 min to obtain carbon-poor alloy powder; S3, preparing a pre-sintered matrix, first wet-milling the carbon-poor cemented carbide powder, the ball milling medium is alcohol, the liquid-solid ratio of alcohol to powder is 400-600mL / kg, the ball-to-material ratio of ball milling is 4-6:1, the ball mill speed is controlled at 50-100 rpm, the ball milling time is controlled at 15-20h, after the wet milling is completed, the slurry is filtered, and a spray dryer is used for atomization drying and granulation, and then the granulated powder is pressed and formed at 150-200MPa, and pressure sintered at 1430-1445°C and a pressure of 8-10 MPa for 50-75 minutes to obtain a carbon-poor pre-sintered matrix; S4, carburizing treatment, placing the pre-sintered substrate in a hydrogen atmosphere, using dense crystalline graphite as a carbon source, and performing carburizing treatment at 1420-1450° C. for 60-100 minutes to obtain a carburized cemented carbide; S5, firing, ball-milling the carburized cemented carbide into powder of 0.1-5 μm, loading it into a cemented carbide mold, and then placing it into a spark plasma sintering device for low-temperature and high-pressure sintering.
3. A novel high wear-resistant and high strength cemented carbide production process according to claim 2, characterized in that: The raw materials prepared in S1 are dried under a vacuum environment.
4. A novel high wear-resistant and high strength cemented carbide production process according to claim 2, characterized in that: The S2 is used to prepare the carbon-poor alloy powder. During the mixing, a dry ball mill is used for mixing. The ball-to-material ratio is controlled at 3:1, the mixing speed is controlled at 50-200 rpm, and the mixing time is controlled at 3-8h.
5. A novel high wear-resistant and high strength cemented carbide production process according to claim 2, characterized in that: The S5 is placed in a spark plasma sintering device for low-temperature and high-pressure sintering, the sintering pressure is controlled at 100-300 MPa, the temperature is increased from room temperature to 100°C, the heating rate is 10-50°C / min, and it is kept at 100°C for 10-30 min. After the insulation is completed, the temperature is increased from 100°C to 300°C, the heating rate is 10-50°C / min, and it is kept at 300°C for 10-30 min. After the insulation is completed, the sintering pressure is increased to 300-500 MPa, and under this pressure, the temperature is increased from 300°C to 500-700°C, the heating rate is 10-100°C / min, and it is kept at 500-700°C for 30-60 min.
6. A novel high wear-resistant and high strength cemented carbide production process according to claim 5, characterized in that: The pre-sintered block in the cemented carbide mold obtained in S5 is placed in a high-strength graphite mold and placed in a spark plasma sintering device for densification sintering, and finally a composite cemented carbide for tool material is obtained.
7. A novel high wear-resistant and high strength cemented carbide production process according to claim 6, characterized in that: The material is placed in a spark plasma sintering device for densification sintering, the sintering pressure is controlled to be 70-240MPa, the heating rate is 50-100°C / min, the sintering temperature is 980-1040°C, and the material is kept at 980-1040°C for 1-3min. After the holding period, the material is cooled to 300°C at a cooling rate of 10-100°C / min, and then cooled to room temperature along with the furnace.
8. A novel high wear-resistant and high strength cemented carbide production process according to claim 4, characterized in that: The S2 raw material mixing comprises the following specific steps: S2.1, put the raw materials into a ball mill for dry ball milling to fully mix the raw materials and obtain mixed powder; S2.
2. Place the mixed powder into a high temperature resistant reaction vessel, and then place it in a hydrogen reduction furnace, ensuring that the vessel is placed stably and has enough space for hydrogen circulation around it; S2.
3. Before heating, slowly introduce hydrogen into the reduction furnace to remove the air in the furnace and prevent oxidation reaction between oxygen and raw materials. The speed of introducing hydrogen needs to be controlled. When the air in the furnace is basically exhausted, speed up the hydrogen flow to maintain a stable hydrogen atmosphere in the furnace. S2.3, turn on the heating device, raise the temperature in the furnace to 900-1050°C at a certain heating rate, and maintain it within this temperature range for 45-75 minutes, so that the oxides in the raw materials undergo a reduction reaction in the hydrogen atmosphere to generate corresponding metals or alloys, thereby obtaining carbon-poor alloy powder; S2.
4. After the reduction reaction is completed, stop heating and allow the furnace to cool naturally or cool to room temperature with the furnace under a protective atmosphere. Stop introducing hydrogen only when the temperature in the furnace drops below the safe temperature. Then carefully take out the reaction vessel to obtain the prepared carbon-poor alloy powder.
9. A novel high wear-resistant and high strength cemented carbide production process according to claim 2, characterized in that: In the material preparation stage, the S1 adopts a vibration ball milling method. Through the high-frequency vibration of the ball mill jar, the grinding balls generate strong vibration impact in the jar, thereby grinding and crushing the powder, thereby controlling the particle size of the raw material.